2016
DOI: 10.1177/1535676016652231
|View full text |Cite
|
Sign up to set email alerts
|

Microbes in Irrigation Water and Fresh Vegetables

Abstract: Irrigated fresh vegetables are a potential portal for dissemination of human pathogens that may be associated with irrigation water source. This study investigated the quality of irrigation water and the fresh vegetables produced in regard to pathogenic bacteria found at a selected vegetable farm in southwestern Nigeria. Enumeration and characterization of total heterotrophic bacteria and potential pathogens (mostly enteric bacteria) were done with international procedures. Susceptibility of the potential path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…As for the bacteria of the genus Klebsiella, their very sticky pink colonies appeared fermenting the sugar lactose on the MacConkey medium, and as for the E.M.B medium, they appeared in a slightly pinkish-orange color. This is consistent with the results of the study [19]. In microbial examination, the isolates were examined in the optical microscope, the results were all Gram-negative bacteria, rod-shaped and short, as shown in Figure .…”
Section: A Diagnosis Of Isolatessupporting
confidence: 89%
“…As for the bacteria of the genus Klebsiella, their very sticky pink colonies appeared fermenting the sugar lactose on the MacConkey medium, and as for the E.M.B medium, they appeared in a slightly pinkish-orange color. This is consistent with the results of the study [19]. In microbial examination, the isolates were examined in the optical microscope, the results were all Gram-negative bacteria, rod-shaped and short, as shown in Figure .…”
Section: A Diagnosis Of Isolatessupporting
confidence: 89%
“…The mean TBC of the irrigation water sample in the present study was 4.2 log CFU/mL. Higher results (5.5 and 7.1 log CFU/mL) were reported in Ibadan, Nigeria, 41 and Hawassa, Ethiopia 9 respectively. The TC level of 3.9 log CFU/mL in the present study is slightly lower than the study reported by Akinde et al, 41 where the mean TC in the irrigation water sample was found to be 4.1 log CFU/mL.…”
Section: Discussioncontrasting
confidence: 56%
“…Higher results (5.5 and 7.1 log CFU/mL) were reported in Ibadan, Nigeria, 41 and Hawassa, Ethiopia 9 respectively. The TC level of 3.9 log CFU/mL in the present study is slightly lower than the study reported by Akinde et al, 41 where the mean TC in the irrigation water sample was found to be 4.1 log CFU/mL. Zavadil 11 also reported higher TC and FC (6.2 and 5.4 log CFU/mL, respectively) values from the irrigation wastewater.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Irrigation is the application of water to the soil during agricultural production of farm produce to maximize the yield of fresh produce, and this is especially done during the dry seasons [90]. Irrigation water is used to supplement inadequate rainfall in many regions of the world, and being a critical requirement for the optimum production of farm produce, it is necessary to irrigate plants whenever needed [91].…”
Section: Preharvest Transmission Routes Of Fresh Produce Associatementioning
confidence: 99%